A Clinician and Clinical Trialist’s Perspective - Hoogwerf, Byron J. (Cleveland Clinic Journal of Medicine, 2008)
The Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial tested the hypothesis that intensive glucose-lowering (with a hemoglobin A1c target of less than 6.0%) would reduce the incidence of atherosclerotic disease events and death compared with standard treatment (with a hemoglobin A1c target of 7.0% to 7.9%) in more than 10,000 patients with type 2 diabetes at high risk of cardiovascular events. The study was terminated early because more people had died in the intensive-treatment group than in the standard-treatment group (257 vs 203). The ACCORD results should not substantially alter our usual approach to glucose-lowering, which should still be “as low as we can get it safely” while avoiding hypoglycemia, significant weight gain, complex regimens, and, perhaps, the “stress” of maintaining glycemic control, especially in patients at high risk of coronary heart disease.